Perbandingan Strategi Pembelajaran Aktif Tipe Everyone Is A Teacher Here dan Tipe The Power Of Two terhadap Hasil Belajar Biologi Siswa Kelas VIII SMPN 2 Ampek Angkek - Rahmadina, Lia; Sudirman, Sudirman; Amri, Erismar (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The background of this research was the studentâs of class VIII SMPN 2 Ampek Angkek low biology test outcome, due to the less motivated studentâs. The teachers tended to give long explanation, it led into the teachers center process in teaching and learning. The students were less confident for questions and answer. The purpose of the research was to find out the comparison of students biology test result by using active learning strategy type everyone is a teacher here and type the power of two to the class VIII students of SMPN 2 Ampek Angkek. The research has been done in class VIII on August 2013. This type of research was experimental research by randomized control group posttest only design. The population of this research were all students of class VIII SMPN 2 Ampek Angkek listed in the academic year 2013/2014. Test used was an objective test. The technique of data analysis was t test. Based on the data analysis result, it was found that both of the sample classes were normal distribution and homogeny. The result of hypothesis test was t score 1,61 meanwhile t table 1,68, it indicates that t score < t table, so the hypothesis of this research was accepted H0, it can be concluded that there was no difference between the type of the active learning strategy everyone is a teacher here and the power of two toward the students tes result.Â